The Role of Human Development Index and Demographic Indices in Facing Global Trade Challenges - Rasam, Fadli; Murti, Wahyu; Rozali, Muhammad (PT FORMOSA CENDEKIA GLOBAL, 2024)
When there is world economic instability, innovation and change and adaptation are needed. In an era of rapidly changing global trade, countries with high HDI have a better ability to adapt to market and technological changes, which is important to remain competitive. The aim of this research is to determine the role of HDI and Demography in global trade. The article can also explain the factors that need to be considered in facing global trade in the future. The method used is the literature review method. The steps taken are identifying problems, collecting sources, extracting sources, selecting sources, analyzing sources and drawing conclusions. The important role of human development and demographic indices is labor productivity, the need for innovation and creativity in the quality of education. Labor availability also determines the readiness and supply of various needs and products. A large young population can provide sufficient labor to support the growth of industry and commerce. Countries with growing populations usually have larger labor forces, allowing them to increase production capacity. The government is advised to implement friendly and competitive trade and investment policies. Demography helps governments formulate policies that support trade